OBSTRUCTED PAN CAKE KIDNEY IN A CHILD MANAGED BY IMAGE GUIDED PERCUTANEOUS NEPHROSTOMY - Kumar, Sheo; Mishra, Prabhaker; Singh, Swish Kumar (Journal of Drug Delivery and Therapeutics, 2018)
Pancake kidney, also called pelvic fused kidney, lump or cake kidney, is a rare type of congenital renal fusion anomaly. It is characterized by the presence of a lobulated pelvic renal mass which has a dual parenchymatous system without an intervening septum. Pancake kidney is prone to obstruction due to abnormal rotation of collecting system and calculus. When a patient presents with a nonfunctioning and obstructed kidney, a temporary nephrostomy preserves any recoverable renal tissue. Many a times a seemingly alarming radiological appearance where little functional recovery is expected, dramatic improvement in renal function has been noticed. We report a case of pancake kidney with right PUJ and left ureteric calculus causing hydronephrosis in a 9-years-old male child, evaluated by ultrasonography and MDCT, underwent image guided (sonography and fluoroscopy) percutaneous nephrostomy for relieving the ureteric obstruction. Keywords: Renal fusion, pancake kidney, percutaneous nephrostomy, nephrostogram.